2017
DOI: 10.2147/dddt.s126464
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin induces protective autophagy through activation of BECN1 in human bladder cancer cells

Abstract: PurposeCisplatin-based chemotherapy is the first line treatment for several cancers including bladder cancer (BC). Autophagy induction has been implied to contribute to cisplatin resistance in ovarian cancer; and a high basal level of autophagy has been demonstrated in human bladder tumors. Therefore, it is reasonable to speculate that autophagy may account for the failure of cisplatin single treatment in BC. This study investigated whether cisplatin induces autophagy and the mechanism involved using human BC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 44 publications
6
93
0
Order By: Relevance
“…Recent studies have reported that UVRAG not only promotes Beclin‐1‐mediated autophagy, but it also facilitates endosome/autophagosome maturation . Activation of autophagy can increase chemo‐ and radiotherapy resistance in bladder cancer . We also found that high expression of UVRAG predicted poor prognosis, which was consistent with the role of circUVRAG.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recent studies have reported that UVRAG not only promotes Beclin‐1‐mediated autophagy, but it also facilitates endosome/autophagosome maturation . Activation of autophagy can increase chemo‐ and radiotherapy resistance in bladder cancer . We also found that high expression of UVRAG predicted poor prognosis, which was consistent with the role of circUVRAG.…”
Section: Discussionsupporting
confidence: 86%
“…18,19 Activation of autophagy can increase chemo-and radiotherapy resistance in bladder cancer. [20][21][22] We also found that high expression of UVRAG predicted poor prognosis, which was consistent with the role of circUVRAG.…”
Section: Discussionsupporting
confidence: 84%
“…Cell culture, antibodies, and reagents Cisplatin-resistant bladder cancer cell line, N/P (14), was a gift from Dr. Tzyh-Chyuan Hour (Kaohsiung Medical University) (25), and CWR22Rv1-GFP-LC3 cells was from Dr. Hsing-Jien Kung in 2015 (Taipei Medical University) (26). RT-112 and RT-4 cells were purchased and cultured as previously described (24), and were not further authenticated by us.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, autophagy is reportedly related to bladder cancer grade, and inhibition of high basal level of autophagy results in apoptotic cell death (12,13). Meanwhile, autophagy also contributes to cisplatin resistance in bladder cancer cells (14). Therefore, the discovery of novel autophagy inhibitors should provide therapeutic potential to patients with bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to apoptosis, cisplatin has been reported to induce autophagy in lung, esophageal, and ovarian cancer cells (Xu et al, 2012;Yu et al, 2014;Wu et al, 2015). Moreover, low dose of cisplatin also could induce autophagy in lung-cancer cells (5 µM) and bladder cancer cells (6.25 µM) (Cho et al, 2014;Lin et al, 2017). However, inhibitor of autophagy promotes cisplatininduced apoptosis (Xu et al, 2012;Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%